Students perceptions of cheating behavior - Basuki Roswanto; Alif Vianni Namina; Arina Athiyallah (Priviet Social Sciences Journal, 2025)
This study aims to explore students perceptions of cheating behavior and the factors that influence these actions. Using a qualitative approach with phenomenological methods, data were collected through in-depth interviews with two high school students in the Islamic boarding school environment, each representing cheating behavior and academic integrity. The results showed that although both respondents realized that cheating was wrong behavior, there was a difference in consistency between moral understanding and actual behavior. Internal factors such as self-efficacy and motivation, and external factors such as academic pressure, peer environment, and weak supervision systems, also affect the tendency to cheat. These findings were analyzed through the framework of Bandura's social cognitive theory, which emphasizes the importance of the role of the environment and self-confidence in shaping behavior. This study has important implications for educational institutions to build systems that foster academic honesty and integrity.